Current state and prospects of dihydroquercetin application in food industry - A. A. Ushkalova; T. Zhang; L. Baochen (Пищевые системы, 2024)
This review is a detailed analysis of the results of the experimental studies carried out by scientists from different countries and devoted to the practical application of dihydroquercetin in food products. The main attention is paid to the antioxidant and functional properties of the bioflavonoid in the composition of milk and dairy products. Currently, dihydroquercetin is considered the most powerful natural antioxidant, which use prolongs the shelf-life of products and has a beneficial effect on the human body. Although much time has passed since dihydroquercetin discovery by Russian scientists, today a significant part of research of the bioflavonoid is focused on the pharmaceutical sphere, while its use in the food industry is at the initial stage of the development. In the article, studies carried out by Russian, Chinese, Japanese, European, American and other foreign authors are systemized, which allowed describing quite thoroughly trends in the use of dihydroquercetin in the global industry. Having focused on the influence of the antioxidant on the characteristics of dairy products, scientists found that it increases the stability of acidity and pH, inhibits the development of the pathogenic microflora, favorably affects taste and aroma. Prospect directions for its use have been revealed, and directions for further research of the use of this antioxidant in the dairy industry have been identified. It is concluded that the addition of dihydroquercetin into a recipe will allow obtaining new functional (parapharmaceutical) food products with the antioxidant stability to prevent socially significant diseases and improve the health of the population.